Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.celrep.2020.107599
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Human Neural Stem Cells Generating Organizer States In Vitro before Committing to Cortical Excitatory or Inhibitory Neuronal Fates

Abstract: SUMMARY Better understanding of the progression of neural stem cells (NSCs) in the developing cerebral cortex is important for modeling neurogenesis and defining the pathogenesis of neuropsychiatric disorders. Here, we use RNA sequencing, cell imaging, and lineage tracing of mouse and human in vitro NSCs and monkey brain sections to model the generation of cortical neuronal fates. We show that conserved signaling mechanisms regulate the acute transition from proliferative NSCs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 131 publications
1
11
0
Order By: Relevance
“…1E , F and S2E , Table S3 ) (Hanashima et al, 2004; Muzio and Mallamaci, 2005). Therefore, the hem organizer‘s role for the development of the mammalian cortical plate fate in vivo (Caronia- Brown et al, 2014) and in human stem cell differentiation in vitro (Micali et al, 2020) was reproduced in organoids. The MCP included both putative ependymal cells (GMNC+, FOXJ1+) and choroid plexus cells (TTR+, cluster 15) ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E , F and S2E , Table S3 ) (Hanashima et al, 2004; Muzio and Mallamaci, 2005). Therefore, the hem organizer‘s role for the development of the mammalian cortical plate fate in vivo (Caronia- Brown et al, 2014) and in human stem cell differentiation in vitro (Micali et al, 2020) was reproduced in organoids. The MCP included both putative ependymal cells (GMNC+, FOXJ1+) and choroid plexus cells (TTR+, cluster 15) ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, high fraction of IN was associated with expression of TFs of the RG-LGE lineage (e.g., GSX2, SIX3, DLX1/2 ). In contrast, the abundance of EN-PP was driven by a different set of TFs linked to more medial regions of the pallium, including ZIC1 and PROX1, expressed in the cortical hem organizer (Inoue et al, 2008; Micali et al ., 2020). ZIC1 is an activator of WNT signaling (Merzdorf and Sive, 2006), and consistently, expression of several other activators of the WNT signaling pathway ( WLS, WNT7B ) in RG cells were also predictors of EN-PP abundance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Organoids were directed towards a dorso-caudal or antero-ventral telencephalic identity by modulating RSPO3- and FGF8-induced patterning signaling, respectively. Treatment was done during their early differentiation (day in vitro, DIV8-21) when neuroepithelial cells form telencephalic organizer states ( 40 ). Then, organoids were cultured with the same basal differentiation medium and analyzed at DIV35.…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptomic architecture of self-organization that we define here allows mapping of regional embryonic signatures within hPSCs preceding the full expression of classical organizer cell types. We have previously reported a regional neural fate bias spanning the dorso-ventral telencephalic axis, which was also divergent in hiPSC lines from a single donor (15). We showed that this lineage bias in neural stem cells resulted from the differential emergence of transcriptomic signatures that led to the formation of the dorso-caudal organizer, the cortical hem, or the antero-ventral domain identity.…”
Section: Discussionmentioning
confidence: 98%
“…The urgency to address this need is illustrated by recent work reporting developmental differences between hPSC lines in generating regionally specified neural precursors and their possible implications in the etiology of neurodevelopmental disorders (14)(15)(16)(17)(18)(19)(20)(21). Here we employ cellular and genomic approaches to define functionally relevant variation in hPSC lines during in vitro morphogenesis as they traverse the earliest events in forebrain and hindbrain development.…”
Section: Introductionmentioning
confidence: 99%